2022
DOI: 10.1002/ana.26478
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal Hemorrhage Rate Is Associated with Time to Reperfusion and Outcome

Abstract: Objective Despite a 90% reperfusion rate, only 50% of patients with anterior circulation large vessel occlusion‐related acute ischemic stroke (LVO‐AIS) have a functional recovery at 3 months. Parenchymal hematoma (PH) is a predictor of poor outcome after endovascular treatment (EVT). We aim to investigate the relationship between the delay from onset to reperfusion, the occurrence of PH, and functional outcome. Methods The Endovascular Treatment in Ischemic Stroke (ETIS) registry is an ongoing prospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The limited statistical power of their analysis might have influenced the non-significance (study population in this publication: n=285 including 85 patients in the fast progressors subgroup). In previous publications, extended time from stroke onset to reperfusion and lower initial ASPECTS has been separately reported associated with parenchymal hemorrhage occurrence 17 18. Studying stroke progression velocity actually allows regrouping of these two characteristics into a unique indicator that might be a more sensitive and individualized feature for ICH risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The limited statistical power of their analysis might have influenced the non-significance (study population in this publication: n=285 including 85 patients in the fast progressors subgroup). In previous publications, extended time from stroke onset to reperfusion and lower initial ASPECTS has been separately reported associated with parenchymal hemorrhage occurrence 17 18. Studying stroke progression velocity actually allows regrouping of these two characteristics into a unique indicator that might be a more sensitive and individualized feature for ICH risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only limited and discrepant data regarding the impact of EVT time metrics on sICH occurrence. In a recently published prospective observational study, the rate of parenchymal hematoma increased by 2.5% (95% CI 1.5-3.6%, p < 0.001) for every additional hour of onset to reperfusion delay in patients with successful reperfusion (TICI2b-3) [29]. On the contrary, in two studies that compared the neurological outcomes of patient groups treated with drip-and-ship paradigm and in mothership site, the longer onset to reperfusion time of the drip-andship group was not associated with higher risk of overall intracranial hemorrhage or sICH [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Differences with the present study include a larger population, allowing subgroup analyses, particularly in the TICI 2b subgroup (239 patients vs 1,071 patients in the present analysis). Recently, Olivot et al evaluated the relationship between TSOR and the occurrence of PH with functional outcome, and found that parenchymal hemorrhage (PH) rate is strongly associated with TSOR and affects functional outcome (ie, “time is bleeding”) 30 . It is therefore possible that the relationship between TSOR and functional outcome according to the reperfusion status is also mediated by PH occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Olivot et al evaluated the relationship between TSOR and the occurrence of PH with functional outcome, and found that parenchymal hemorrhage (PH) rate is strongly associated with TSOR and affects functional outcome (ie, "time is bleeding"). 30 It is therefore possible that the relationship between TSOR and functional outcome according to the reperfusion status is also mediated by PH occurrence. Further studies will be needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%